Tracking Valued and Avoidant Functions with Health Behaviors: A Randomized Controlled Trial of the Acceptance and Commitment Therapy Matrix Mobile App. Issue 1 (January 2022) - Levin, Michael E.; Krafft, Jennifer; Seifert, Seth; Lillis, Jason
This randomized controlled trial evaluated the acceptability and additive effects of self-monitoring avoidant and valued functions of behavior, in the context of self-monitoring physical activity and dietary behavior in a mobile app. The self-monitoring approach was based on the Acceptance and Commitment Therapy (ACT) Matrix. A sample of 102 adults interested in improving their diet and physical activity were randomized to a Health Behavior Tracking app (HBT), HBT plus ACT matrix app (HBT+ACT), or waitlist condition. Online self-report assessments were completed at baseline, mid (2 weeks), and post-intervention (4 weeks). Participants reported high usability, but mixed satisfaction with both apps. About half of the prompted app check-ins were completed on average, with 14% never using the ACT app. Participants in the HBT+ACT app condition reported greater self-reported physical activity over time relative to HBT and waitlist, potentially due to protecting against a decrease over time in physical activity observed in the other two conditions. HBT and HBT+ACT conditions both improved self-reported sedentary behavior relative to waitlist. HBT+ACT improved cognitive restraint with eating more than HBT. Neither the HBT or HBT+ACT app improved other health behavior outcome measures or values processes relative to the waitlist. Overall, findings suggest some benefits of the ACT Matrix app for addressing physical activity by tracking valued/avoidant functions, but mixed findings on acceptability, outcomes, and processes of change suggests impact may be relatively limited.